1996
DOI: 10.1021/bi961606w
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Binding of Phospholipases C-β1 and C-β2 Is Independent of Phosphatidylinositol 4,5-Bisphosphate and the α and βγ Subunits of G Proteins

Abstract: We have measured the membrane binding affinities of purified phosphatidylinositol-specific phospholipases C-beta 1 and C-beta 2 to membranes of varying lipid composition using fluorescence methods. Our studies show that these proteins bind with affinities of 10(-5)-10(-4) M, with a small dependence on lipid type. Binding was relatively insensitive to the presence of phosphatidylinositol-specific phospholipases C-beta s' major physiological substrate, phosphatidylinositiol 4,5-bisphosphate, as well as the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
6

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 49 publications
7
107
6
Order By: Relevance
“…Recombinant human PLC-␦ 1 expressed in Escherichia coli, a generous gift from Dr. Mario J. Rebecchi, was purified as described elsewhere (22). Recombinant PLC-␤ 1 expressed in Sf9 cells, a generous gift from Dr. Suzanne Scarlata, was purified as described elsewhere (23).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant human PLC-␦ 1 expressed in Escherichia coli, a generous gift from Dr. Mario J. Rebecchi, was purified as described elsewhere (22). Recombinant PLC-␤ 1 expressed in Sf9 cells, a generous gift from Dr. Suzanne Scarlata, was purified as described elsewhere (23).…”
Section: Methodsmentioning
confidence: 99%
“…However, in contrast to PLC-δ1, PLC-β2 as well as PLC-β1, bind to membranes with high affinity but little specificity, independent of PI(4,5)P 2 [37][38][39] . Their isolated PH domains are unable to bind to Ins(1,4,5) P 3 [33] but, together with the C-terminal region [38], allow PLC-β1 and PLC-β2 to interact non-specifically with membranes [40].…”
Section: Pleckstrin Homology (Ph) Domainsmentioning
confidence: 98%
“…This binding was thought to activate the PLC-βs by recruiting them to the membrane surface [62]. In contrast, heterotrimeric G proteins activate PLC-βs without promoting its binding to membranes [37,39] and also without affecting the calcium dependence of its activity [10,37,38]. Instead, the strength of activation of PLC-β2 and -β3, at least by Gβγ subunits, appears to be directly proportional to the strength of association between the proteins [63].…”
Section: Protein Activators Of Plc-βsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, G␤␥ may directly stimulate the catalytic activity of these proteins. For example, it has been shown that translocation is not necessary for G␤␥-mediated PLC␤2 activation in vitro (14,15).…”
mentioning
confidence: 99%